A Complete Occlusion of Right Coronary Artery Due to Stanford Type A Aortic Dissection - Successful Treatment with Extracorporeal Membrane Oxygenation (ECMO) - Wang,Yong (2019)
Abstract We present a patient diagnosed Stanford Type A aortic dissection, who was misdiagnosed as acute myocardial infarction for 5 days. In the surgery, the right coronary ostium was totally occluded, and the right coronary artery (RCA) was bluish from the trunk to branches. The true lumen couldn’t be found when we opened the RCA. We had to give up coronary artery bypass grafting (CABG). After a regular surgery of type A aortic dissection, the patient was failed to wean from cardiopulmonary bypass due to the right heart dysfunction. The Extracorporeal membrane oxygenation (ECMO) was instituted. The right ventricular wall motion was gradually improved during the post-operation period. This is the first report of using ECMO to successfully treat a complete occlusion of the right coronary artery due to a Type A aortic dissection. This case demonstrates the value of ECMO in assisting right heart function to ensure stable hemodynamics and myocardial recovery in the type A aortic dissection with coronary involvement.